Pengaruh Kompensasi, Motivasi, Gaya Kepemimpinan, Dan Lingkungan Kerja Terhadap Peningkatan Kinerja Karyawan Di PT Makmur Berkat Solusi - Muhamad Ma'ruf; Jumadi (Jurnal Ekonomi dan Bisnis Digital, 2025)
This study aims to comprehensively explore the influence of compensation, motivation, leadership style, and work environment on employee performance improvement at PT Makmur Berkat Solusi. The research employed a quantitative approach with total sampling of 35 employees. Data were collected using a Likert-scale questionnaire and analyzed through validity and reliability tests, multiple linear regression, t-tests, F-tests, and determination coefficients (R²). The results indicate that all four independent variables positively and significantly affect employee performance both partially and simultaneously. These findings imply the importance of developing human resource management strategies through competitive compensation, targeted motivation, adaptive leadership, and a supportive work environment to enhance employee productivity and well-being.